EVALUATION OF FUEL CONSUMPTION DUE TO WAITING TIME OF LOADING AND HAULING EQUIPMENT AT PIT B BENGALON PT DARMA HENWA TBK - AÃ‚Â’la Zagarino (NIM : 12114082), Firas
PT Darma Henwa Tbk (PTDH) is a coal mining contracting company which is operating in Bengalon, East Kalimantan. As a contractor, PTDH has a challenge to optimize its operational activities so that profits can be maximized. The core of mining activities is loading and hauling activities so that the biggest cost in mining operations is fuel consumption. It was suspected that PTDH often suffered losses from fuel consumption. Therefore, studies on the relationship of fuel usage and match factor must be carried out. In order to determine the match factor, the cycle time of all loading and operating equipment are collected. Based on match factor, the waiting time of the equipment is calculated. By using the equation of the fuel burning ratio, the costs incurred from wasted fuel can be calculated. From these calculations, it can be seen that the EX6008 fleet is the most efficient fleet in consuming fuel. Estimated cost of fuel consumption from fleet EX6008 is Rp. 12,888,484.94.